Die Ikonographie Palästinas/Israels und der Alte Orient Eine Religionsgeschichte in Bildern - Schroer, Silvia (Schwabe Verlag, 2018)
"This forth volume of "Die Ikonographie Palästinas/Israels und der Alte Orient (IPIAO)" is on Iron Age until the beginning of the Achaemenid's rule. Almost 1000 objects of the pictorial art of Palestine / Israel are compared to the pictures of the neighbouring cultures. "